Respuestas

2012-03-30T19:32:14+02:00

a) 3x - 2 (x + 3) = x - 3 (x + 1) 

    3x - 2x - 6 = x - 3x - 3

    3x - 2x - x + 3x = -3 + 6

    3x = 3 | : 3

    x = 1

 

b) 4 + x - 4 (1 - x) + 5 (2 + x) = 0

    4 + x - 4 + 4x + 10 + 5x = 0

    x + 4x + 5x = -4 + 4 - 10

    10x = - 10 | : 10

    x = -1

 

c) 2x + 7 - 2 (x - 1) = 3 (x + 3)

    2x + 7 - 2x + 2 = 3x + 9

    2x - 2x - 3x = 9 - 7 - 2

   - 3x = 0

esta ecuación es incompatible


d) 4 (2x - 7) - 3 (3x + 1) = 2 - 7x

    8x - 14 - 9x - 3 = 2 - 7x

    8x - 9x + 7x = 2 + 14 + 3

    6x = 19 | :6

    x = 19/6

    x = 3 1/6

¡La mejor respuesta!
2012-03-30T20:08:10+02:00

buenas tardes:3x-2(x+3)=x-3(x+1) ejercico(a)
                     : 3x-2x-6=x-3x-3
                     :3x-2x-x+3x=-3+6

                     :3x=3
                     :x=3/3=1

                     :x=1

comprobacion:3(1)-2(1+3=1-3(1+1)
                     :3-2-6=1-3-3
                     :-5=-5


ejercicio(b) 4+x-4(1-x)+5(2+x)=0
                  4+x-4+4x+10+5x=0

                  x+4x+5x=0+4-10
                  10x=-6
                   x=-6/10 simplifico entre 2 y obtengo:

                   x=-3/5

comprobacion:4+(-3/5)-4(1-(-3/5))+5(2+(-3/5))=0

                     :4+(-3/5)-4+4(-3/5)10+5(-3/5)=0
                     :  -3/5+4(-3/5)+5(-3/5)=0+4-10
                     :10(-3/5)=-6
                     :-3/5=-6/10=-3/5
                     :-3/5=-3/5
ejercicio(c) 2x+7-2(x-1)=3(x+3)

                  2x+7-2x+2=3x+9

                  2x-2x-3x=9-7-2

                  -3x=0
                   x=0/3

                  x=0

comprobacion:2(0)+7-2(0-1)=3(0+3)

                     :0+7-0+2=0+9
                     :7+2=9
                     :9=9

ejercicio(d) 4(2x-7)-3(3x+1)=2-(7x)
                  8x-28-9x-3=-14x

                  8x-9x+14x=3+28
                  11x=31
                   x=31/11
comprobacion: 4(2(31/11-7))-3(3(31/11+1))=2-(7(31/11))
                     :8(31/11)-28-9(31/11)-3=-14(31/11)
                     :8(31/11)-9(31/11)14(31/11)=3+28

                     :11(31/11)=31

                     :31/11=31/11

espero     haberte ayudado.